Faktor-Faktor Pengendalian Internal Terhadap Akuntabilitas Laporan Keuangan - Nour Riza Kurniawan (Jurnal Literasi Akuntansi, 2022)
Purpose: This study aims to prove the factors of internal control on the accountability of financial statements.Method: The sample used in this study was a structural official at one of the universities in Indonesia. Data retrieval using a questionnaire with google form media amounted to 33 respondents. The method used is census. The test of this research was carried out using multiple linear regression analysis.Finding: The results showed that partially the control environment, risk assessment, information and communication, and monitoring activities had no effect on the accountability of financial statements. Control activities have a positive effect on financial statement accountability.Novelty: This study considers the effectiveness of the implementation of internal control as a factor that affects the accountability of financial statements at one of the universities in Indonesia.